Ecological Distribution of the Shrimp Nematopalaemon Schmitti (Crustacea: Decapoda: Caridea) in Three Bays on the South-eastern Coast of Brazil - Almeida, A. C. [UNESP]; Fransozo, A. [UNESP]; Teixeira, G. M. [UNESP]; Hiroki, K. A.N. [UNESP]; Furlan, M. [UNESP]; Bertini, G. [UNESP] (National Inquiry Services Center (NISC), 2012)
The relationships between the spatial and temporal variations in the abundance of the shrimp Nematopalaemon schmitti and water temperature, salinity, and texture and organic-matter content of the sediment, were analysed in Ubatumirim, Ubatuba and Mar Virado bays on the northern coast of São Paulo, Brazil. Sampling was carried out monthly, from January 1998 through December 1999, from a shrimp boat equipped with double-rig nets, along six transects in each bay. In total, 2 116 specimens of N. schmitti were caught. Their distribution differed among bays, transects and seasons (ANOVA, p < 0.05). Highest total abundance was found in areas of high organic-matter content, in substrate composed mainly of very fine sand and silt and clay, and during winter and autumn. Although multiple regression analysis showed no significant relationship (p > 0.05), observations suggest that water temperature, sediment texture, organic-matter content, and the presence of biodetritus and plant fragments, provided favourable environmental conditions for the establishment of N. schmitti in the region. © 2012 Copyright NISC (Pty) Ltd.
Keywords: abiotic factors; abundance; spatial variation; temporal variation